Timely Inhibition of Notch Signaling by DAPT Promotes Cardiac Differentiation of Murine Pluripotent Stem Cells - Liu, Yinan; Li, Peng; Liu, Kaiyu; He, Qihua; Han, Shuo; Sun, Xiaofeng; Li, Tao; Shen, Li (PLOS ONE, 2014)
The Notch signaling pathway plays versatile roles during heart development. However, there is contradictory evidence that Notch pathway either facilitates or impairs cardiomyogenesis in vitro. In this study, we developed iPSCs by reprogramming of murine fibroblasts with GFP expression governed by Oct4 promoter, and identified an effective strategy to enhance cardiac differentiation through timely modulation of Notch signaling. The Notch inhibitor DAPT (N-[N-(3,5-difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester) alone drove the iPSCs to a neuronal fate. After mesoderm induction of embryoid bodies initiated by ascorbic acid (AA), the subsequent treatment of DAPT accelerated the generation of spontaneously beating cardiomyocytes. The timed synergy of AA and DAPT yielded an optimal efficiency of cardiac differentiation. Mechanistic studies showed that Notch pathway plays a biphasic role in cardiomyogenesis. It favors the early–stage cardiac differentiation, but exerts negative effects on the late-stage differentiation. Therefore, DAPT administration at the late stage enforced the inhibition of endogenous Notch activity, thereby enhancing cardiomyogenesis. In parallel, DAPT dramatically augmented the expression of Wnt3a, Wnt11, BMP2, and BMP4. In conclusion, our results highlight a practicable approach to generate cardiomyocytes from iPSCs based on the stage-specific biphasic roles of Notch signaling in cardiomyogenesis.